Effect of plasma power on the structural properties of tin oxide prepared by plasma-enhanced atomic layer deposition. Issue 6 (15th March 2021) - Hsu, Chia-Hsun; Zhang, Zhi-Xuan; Huang, Pao-Hsun; Wu, Wan-Yu; Ou, Sin-Liang; Lien, Shui-Yang; Huang, Chien-Jung; Lee, Ming-Kwei; Zhu, Wen-Zhang
Abstract: In this study, tin oxide (SnO2 ) films are prepared by using plasma enhanced atomic layer deposition (PEALD) with tetrakis(dimethylamino)tin(IV) (TDMA-Sn) as the Sn metal source and O2 /Ar mixture as the oxidant. The plasma power is varied from 1000 to 3000 W to investigate its influence of oxygen vacancies and defects on the SnO2 film properties. The experimental results show that the plasma power plays an important role in the deposition of SnO2 films. Unwanted Sn3 O4 formation is observed at both of low and high powers. The optical emission spectra of the plasma with different power are analyzed to obtain the insight of the mechanism of the PEALD SnO2 films growth. The optimal plasma power of 1500 W is found to be very close to the threshold where the oxygen radical intensity starts to sharply increase. Lower and higher powers can lead to insufficient oxidation and strong ion bombardment, respectively, resulting in reduced SnO2 film quality.